2021
DOI: 10.1038/s41525-021-00207-7
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 activates lncRNA DANCR and inhibits cancer cell autophagy accelerating gastric cancer progression

Abstract: Cancer cell autophagy has been associated with the progression of gastric cancer (GC), but involvement of long noncoding RNAs (lncRNAs) remains unclear. Initial bioinformatics analysis has identified abnormally highly expressed KLF5 in GC, as well as the predicted regulatory mechanism associating with lncRNA DANCR, miR-194, and AKT2. The expression of KLF5, DANCR, and AKT2 in GC tissue was upregulated, and the expression of miR-194 was downregulated. We knocked KLF5 down and manipulated the expression of DANCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“… 8 Wang et al found that lncMALAT1 can promote IL-6 secretion by blocking autophagy flux in GC cells, causing the activation of normal to cancer-related fibroblast transformation, which plays an important role in the development of GC. 45 In a similar study, Chen et al reported that the expressions of KLF5 and lncDANCR were up-regulated in GC tissues, 18 where KLF5 activated lncDANCR, inhibited autophagy of GC cells, and accelerated the progression of GC. 18 Other autophagy-related lncRNAs play important roles in the occurrence, development, and treatment of GC.…”
Section: Autophagy-related Noncoding Rna and Gastric Cancermentioning
confidence: 89%
See 3 more Smart Citations
“… 8 Wang et al found that lncMALAT1 can promote IL-6 secretion by blocking autophagy flux in GC cells, causing the activation of normal to cancer-related fibroblast transformation, which plays an important role in the development of GC. 45 In a similar study, Chen et al reported that the expressions of KLF5 and lncDANCR were up-regulated in GC tissues, 18 where KLF5 activated lncDANCR, inhibited autophagy of GC cells, and accelerated the progression of GC. 18 Other autophagy-related lncRNAs play important roles in the occurrence, development, and treatment of GC.…”
Section: Autophagy-related Noncoding Rna and Gastric Cancermentioning
confidence: 89%
“…8 The researchers found that LncSNHG11 aggravated oncogenic autophagy to facilitate the stemness, proliferation, migration, invasion, and EMT in GC by activating the Wnt/β-catenin pathway. 8 Wang et al found that lncMALAT1 can promote IL-6 secretion by blocking autophagy flux in GC 45 In a similar study, Chen et al reported that the expressions of KLF5 and lncDANCR were up-regulated in GC tissues, 18 where KLF5 activated lncDANCR, inhibited autophagy of GC cells, and accelerated the progression of GC. 18 Other autophagy-related lncRNAs play important roles in the occurrence, development, and treatment of GC.…”
Section: Autophagy Related Lncrna and Gastric Cancermentioning
confidence: 96%
See 2 more Smart Citations
“…Another study in gastric cancer cells has shown that KLF5 activates DANCR transcription. DANCR could act as a molecular sponge for miR-194 to suppress its expression and increase expression of AKT2, thus promoting gastric carcinogenesis through inhibition of autophagy [ 31 ]. Moreover, expression of DANCR in gastric cancer can be induced by SALL4 [ 32 ].…”
Section: Cell Line Studiesmentioning
confidence: 99%